1974
DOI: 10.1203/00006450-197402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Linear Growth Responses in Hypopituitary Dwarfs Treated with Growth Hormone Plus Androgen versus Growth Hormone Alone

Abstract: ExtractTwelve hypopituitary patients ranging in age from 58f2 to 15 ?fa years were treated for 12 months with a standardized dose of human growth hormone (HGH), 0.1 or 0.05 U/kg three times weekly). From the 7th to 12th month inclusive, fluoxymesterone, 2.5 mg/m2/24 hr per os was given in combination with the growth hormone. From the 12th to the 18th month, no therapy was given. Heights and weights were recorded every 1 or 2 months. Bone age films were assessed at the onset and again in the 6th, 12th, and 18th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1979
1979
1995
1995

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Tanner and Whitehouse [209] sug- Table 3. Androgen therapy in hypopituitary patients Aynsley-Green et al [7] Harada et al [101] McGillivray et al [159] Pertzelan et al [194] Raiti et al [ [210], however, re-evaluated some of the data reported by these groups and concluded growth to be less favourable than with constant GH administration. Though the available results on the final height achieved by comparable groups of patients treated according to either regimen presently do not prove the superiority of one or the other point of view, intermittent therapy should possibly be avoided.…”
Section: Intermittent Therapymentioning
confidence: 93%
“…Tanner and Whitehouse [209] sug- Table 3. Androgen therapy in hypopituitary patients Aynsley-Green et al [7] Harada et al [101] McGillivray et al [159] Pertzelan et al [194] Raiti et al [ [210], however, re-evaluated some of the data reported by these groups and concluded growth to be less favourable than with constant GH administration. Though the available results on the final height achieved by comparable groups of patients treated according to either regimen presently do not prove the superiority of one or the other point of view, intermittent therapy should possibly be avoided.…”
Section: Intermittent Therapymentioning
confidence: 93%
“…Growth hormone therapy increases the hair zinc concentration, and reduces urinary ex cretion of zinc [8]. Synergistic effects of growth hormone and androgen therapy have been reported in the therapy of short children [25][26][27][28],…”
Section: Discussionmentioning
confidence: 99%
“…Both hormones interact with growth hormone in control of the adolescent growth spurt (2)(3)(4). After growth is completed, androgens and estrogens maintain bone mass in the adult.…”
mentioning
confidence: 99%